Biocompatibility and Antibacterial Properties of ZnO-Incorporated Anodic Oxide Coatings on TiZrNb Alloy - Oleksandr Oleshko; Yevheniia Husak; Viktoriia Korniienko; Roman Pshenychnyi; Yuliia Varava; Oksana Kalinkevich; Marcin Pisarek; Karlis Grundsteins; Oksana Pogorielova; Oleg Mishchenko; Wojciech Simka; Roman Viter; et al. (Nanomaterials, 2020)
In a present paper, we demonstrate novel approach to form ceramic coatings with incorporated ZnO nanoparticles (NPs) on low modulus TiZrNb alloy with enhanced biocompatibility and antibacterial parameters. Plasma Electrolytic Oxidation (PEO) was used to integrate ZnO nanoparticles (average size 12–27 nm), mixed with Ca(H2PO2)2 aqueous solution into low modulus TiZrNb alloy surface. The TiZrNb alloys with integrated ZnO NPs successfully showed higher surface porosity and contact angle. XPS investigations showed presence of Ca ions and absence of phosphate ions in the PEO modified layer, what explains higher values of contact angle. Cell culture experiment (U2OS type) confirmed that the surface of as formed oxide-ZnO NPs demonstrated hydrophobic properties, what can affect primary cell attachment. Further investigations showed that Ca ions in the PEO coating stimulated proliferative activity of attached cells, resulting in competitive adhesion between cells and bacteria in clinical situation. Thus, high contact angle and integrated ZnO NPs prevent bacterial adhesion and considerably enhance the antibacterial property of TiZrNb alloys. A new anodic oxide coating with ZnO NPs could be successfully used for modification of low modulus alloys to decrease post-implantation complications.